2019
DOI: 10.1007/s12649-019-00831-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of By-Products Generated from Anaerobic Digestion of Municipal Solid Waste

Abstract: Purpose This study aimed to examine the possibilities of the treatment of the by-products generated in the anaerobic digestion (AD) of the organic fraction of municipal solid waste (OFMSW): oxygen stabilization (composting) of the solid digestate and pretreatment with air stripping of the effluents (liquid digestate and leachate from maturation field and reactors from composting). Methods Oxygen stabilization (OS) was performed in full-scale in a mechanical-biological treatment (MBT) plant using three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Many studies reported 55-65% as the best range of moisture content for composting, explaining that the problem associated with moisture content higher than 65% is the possibility to decrease oxygen diffusion through biomass particles, leading to the activation of anaerobic processes [30][31][32][33]. In this study, two operative parameters were adopted in order to overcome this risk: the air flow rate was kept continuously high (about 0.6 L min −1 kg −1 ) to help oxygen diffusion, while the mechanical turning/mixing of the pile in the sector at the transition from thermophilic to mesophilic conditions allowed a reallocation of particles and air pathways, enabling the access of microorganisms to further sources of organic matter (as noted in the study by Seruga et al [34]). The samples taken from the feedstock pile for the respirometric tests with AIR-nl methodology showed the following values of the maximum 24-h-average dynamic respirometric indexes DRI 24,max (respectively before vs. after composting process): 1340 vs. 340 for MIX 00%, 826 vs. 124 for MIX 25%, 1287 vs. 128 for MIX 50%, 1201 vs. 186 for MIX 75% (values expressed in mg O 2 kg VS −1 h −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported 55-65% as the best range of moisture content for composting, explaining that the problem associated with moisture content higher than 65% is the possibility to decrease oxygen diffusion through biomass particles, leading to the activation of anaerobic processes [30][31][32][33]. In this study, two operative parameters were adopted in order to overcome this risk: the air flow rate was kept continuously high (about 0.6 L min −1 kg −1 ) to help oxygen diffusion, while the mechanical turning/mixing of the pile in the sector at the transition from thermophilic to mesophilic conditions allowed a reallocation of particles and air pathways, enabling the access of microorganisms to further sources of organic matter (as noted in the study by Seruga et al [34]). The samples taken from the feedstock pile for the respirometric tests with AIR-nl methodology showed the following values of the maximum 24-h-average dynamic respirometric indexes DRI 24,max (respectively before vs. after composting process): 1340 vs. 340 for MIX 00%, 826 vs. 124 for MIX 25%, 1287 vs. 128 for MIX 50%, 1201 vs. 186 for MIX 75% (values expressed in mg O 2 kg VS −1 h −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…It prevents any decrease in moisture content during aeration, since the air is constantly kept in a saturated vapor condition, and this is important since humidity affects microbial activity [29][30][31][32][33][34]; a future improvement to avoid high moisture content in final compost could be the recirculation of external air while excluding the water bath in the last days of the process, allowing the dehumidification of the biomass.…”
mentioning
confidence: 99%
“…Besides packaging waste recovery, it allows for collecting biowaste, which may be up to 50% of the municipal waste. Anaerobic digestion (AD) can be thought of as the most promising and sustainable process for the treatment of organic waste [18] and an environmentally friendly method for waste management [19]. In source-segregated biowaste AD, in addition to biogas, added value material is also recovered, which can be used on crops [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the analyzed area, it was a "door-to-door" system regarding rural and single-family housing, with the assumption of disposal in various standard bins in the case of multi-family housing. The OFMSW is generated in the mechanical sorting and separation process performed in mechanical-biological treatment (MBT) plants [12]. Source segregation fits the circular economy concept and is regarded as a landfilling problem solution [12].…”
Section: Introductionmentioning
confidence: 99%
“…The OFMSW is generated in the mechanical sorting and separation process performed in mechanical-biological treatment (MBT) plants [12]. Source segregation fits the circular economy concept and is regarded as a landfilling problem solution [12]. Source-segregated biowaste provides higher recovery potential and treatment process performance compared to OFMSW [13].…”
Section: Introductionmentioning
confidence: 99%